Use of Medication in Outpatient Hypertension Patients - Bulqiah, Andi; Suprapti, Budi; Ardiana, Shafira muti; Alsagaff, M. Yusuf; Suharjono (Window of Health : Jurnal Kesehatan, 2023)
Hypertension is a major risk factor for cardiovascular disease, there are 1.13 billion people in the world suffering from hypertension. Hypertension should be given special consideration due to its impact on both the short and long term, one of which is by providing appropriate pharmacological therapy. The purpose of this study is to ascertain the pattern of medication use in hypertensive patients. The current study is a retrospective observational study that examines drug use patterns in hypertensive patients with or without associated disease. Using time-limited sampling techniques, the study sample is drawn from an electronic prescription of outpatient hypertension patients at Universitas Airlangga Surabaya Hospital (RSUA) in March 2021. According to the findings of this study, the most frequently prescribed antihypertensive medications were beta-blockers (29,66 %), ARB (27,51 %), CCB (26,17 %), aldosterone antagonists (6,72 %), loop diuretics (5,78 %), ACEi (3,98 %), and central α2 agonists (3,98 %) (0,14 % ). Antihypertension medications are prescribed singly or in combination. In hypertensive patients with co-morbidities, drugs other than antihypertensives will be prescribed to treat the co-morbidities. The most frequently prescribed non-antihypertensive drugs are antihyperlipidemia statin (45,1 %), platelet antiagregation (19,1%), and antiangina (13,8 %). The study concludes that antihypertension medications are used alone or in combination with up to five other antihypertensive medications, with the most common combination being three drugs in 45% of patients. Suggestions for this study are that it should be accompanied by direct patient identification to minimize the incidence of drug interactions and drug side effects in patients.